Konsep Literasi Digital dalam Kurikulum Merdeka Belajar pada Era Disrupsi di Sekolah Dasar: Kajian Buku “Literasi Digital dalam Dunia Pendidikan di Abad ke-21” Karya Daniel Ginting - Lupita Atika Rachma (EL-Hadhary: Jurnal Penelitian Pendidikan Multidisiplin, 2025)
The era of disruption is marked by the rapid development of ICT, education is required to adapt through a change in mindset from a fixed mindset to a growth mindset in order to create effective, efficient, and relevant learning. The use of ICT in schools, such as e-report cards and digital-based learning has become a necessity in line with the demands of generation Z and alpha who are growing up in a digital environment. However, major challenges are still faced, especially the low digital literacy of teachers and students which has an impact on the quality of learning. Digital literacy, which includes technical skills, critical thinking, and responsible use of digital media, needs to be strengthened through training and integration in the independent curriculum. The book "Digital Literacy in the World of Education in the 21st Century" by Daniel Ginting et al. is an important foundation in understanding digital literacy strategies in elementary schools that involve access, analysis, evaluation, creation, and participation in digital media. Therefore, this study aims to find out the concept of digital literacy in the independent learning curriculum in the era of disruption in elementary schools to study the book "Digital Literacy in the World of Education in the 21st Century" by Daniel Ginting et al., to find out the criteria, types, and functions of digital literacy in the independent learning curriculum in elementary schools, and to find out the content of learning materials in the independent learning curriculum in elementary schools that can be integrated with literacy digital. This study uses a qualitative library research method with a qualitative content analysis approach influenced by the naturalistic-interpretive paradigm. The two sources of research data obtained, namely primary data sources in the form of the thoughts of figures and works by Daniel Ginting et al. as authors of the book "Digital Literacy in the World of Education in the 21st Century" in 2021 and secondary data sources in the form of the book "Digital Literacy and Mobile Learning" by Usman et al. and the book "Digital Literacy in Education: Integration and Innovation" by Ganjar Winata Martoatmodjo et al. The research uses documentation data collection techniques and qualitative content analysis techniques used in this study are discourse analysis techniques. The results of the study show that the book by Daniel Ginting et al. entitled "Digital Literacy in the World of Education in the 21st Century" contains the concept of digital literacy which includes five main competencies, namely access, analysis, evaluation, creation, and participation in the use of digital technology. Digital literacy in the independent learning curriculum functions not only as a technical skill, but also as a foundation in forming critical, collaborative, creative, and responsible thinking skills in the use of digital technology. This study also found that elementary school subjects that have implemented an independent learning curriculum from grades 1-6, such as Indonesian, PPKn, English, Science, Social Studies, SBdP, Mathematics, and the P5 project are very relevant to be integrated with digital literacy. Thus, digital literacy can be a key element in supporting learning transformation that is adaptive to technological developments and the needs of the times. Keywords: Digital Literacy, Independent Learning Curriculum, Era of Disruption, Elementary School, Book Study